Indigenous Governance Clans, Constitutions, and Consent - Wilkins, David E. (Oxford University Press, Incorporated, 2023)
Indigenous Governance is a comprehensive overview and critical assessment of the governing methods utilized by the senior sovereigns within North America. Author David E. Wilkins provides detailed examination of the origins, evolution, and structures of these governments and scrutinizes the many diverse arrangements employed by the nearly 600 contemporary Indigenous nations, including the more than 200 Alaska Native communities and the complex, rapidly evolving situation of Native Hawaiians